FIRST AID TRAINING IN ACCIDENT FOR SENIOR HIGH SCHOOL STUDENTS: EFFORTS TO IMPROVE STUDENT’S KNOWLEDGE AND SKILLS - Arina Qona'ah; Erna Dwi Wahyuni; Anestasia Pangestu Mei Tyas; Amellia Mardhika; Hikmah Lia Basuni; Anita Dwi Ariyani (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2023)
Introduction: Lamongan is one of the areas on the north coast with very high traffic accident rate. First aid for accident victims is an important part of the management of accident victims. Students who are in the adolescent age group can become first responders for accident victims. The purpose of this community service activity is to increase students' knowledge and skills in providing first aid to accident victims. Methods: First aid training activities for accidents use lecture, discussion, demonstration and role play methods. The training participants were 50 students of SMKN 1 Lamongan. The material presented in the training includes basic life support, dressings and splints as well as evacuation and transportation. Training using audio visual media and teaching aids. Evaluation of the training using the questionnaires given at the beginning and at the end of the training. Results: The results of the pre test showed that 28 students (56%) had low knowledge, while 22 students (44%) had moderate knowledge. The results of the post test after being given education and training to students were as many as 20 students (40%) had moderate knowledge and 30 students (60%) had high knowledge. Conclusion: First aid training for accident victims for SMKN 1 Lamongan students can increase students' knowledge and skills in performing first aid to accident victims. Students are expected to act as first responders for traffic accident victims.